Handbook of couples therapy - Harway, Michele (John Wiley, 2005)
Noted couples therapist Michele Harway brings together other well-known therapists offering guidance to clinicians working with couples. Up-to-date coverage of the most often used treatment models, advice for working with couples along the lifecycle, and guidelines for treating difficult couple problems make this a necessary resource for all couples therapists and mental health professionals working with adult populations.